Membangun Ketahanan Nasional Melalui Penerapan Rule Of Law dan Konstitusi Nasional - Farah Izzati Najlaa; Misya Lova Haqsya; Choyrunisa Cahya Assago; Maulia Depriya Kembara (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The implementation of the rule of law and the national constitution play an important role in building strong and sustainable national resilience. This research aims to provide an in-depth understanding to the younger generation about the crucial role of the rule of law and the national constitution in building a solid state foundation. The method used was a qualitative approach and in-depth interviews with 18 student respondents to understand their views on the rule of law and the national constitution. The interview results show that the younger generation realizes the importance of knowledge about the rule of law and the national constitution in preventing corruptive behavior, fighting for justice, and protecting individual rights. The implementation of the rule of law and the national constitution is key in building strong national resilience, so a solid understanding of these legal principles is crucial for the younger generation as future leaders. With a strong legal awareness, the younger generation is expected to become agents of change that strengthen national resilience through active participation and advocacy for the principles of democracy and human rights.